The Influence of User Interface, User Experience and User Trust on Purchase Intention - Hafidzah Aryani; Ratih Amelia; Bethani Suryawardani (Journal of Digital Business and Innovation Management, 2026)
This study aims to examine the influence of User Interface, User Experience, and User Trust on Purchase Intention on the Surabaya Buyer e-Peken Application. The research method uses a quantitative approach with data collected through a five-point Likert scale online questionnaire survey, which will be collected from 196 respondents based on the Lameshow formula calculation. The analysis technique used is Structural Equation Modeling Partial Least Square (SEM-PLS) through SmartPLS software version 4. The results show that User Interface has a positive and significant influence on Purchase Intention with a p-value of 0.001. User Trust also has a positive and significant influence on Purchase Intention with a p-value of 0.00. Conversely, User Experience is not proven to have a significant effect on Purchase Intention with a p-value of 0.218. This indicates that interface quality and user trust are the main determining factors in driving consumer purchasing interest on local government e-commerce platforms, while user experience has not been proven to have a significant direct impact on Purchase Intention on the Surabaya e-Peken Application.